USA IN THE EMERGING SYSTEM OF GLOBAL FINANCIAL REGULATION - V. K. Kulakova (Сравнительная политика)
In the globalizing world of fi nancial and economic interdependence, a polycentric, multi-level, and hierarchical system of global financial regulation is emerging. The article highlights two vectors of recent development in international fi nancial regulation: the rise of cooperation through the mechanisms of the Group of Twenty (G-20) on the one hand, and the efforts to maintain the US leading role in global fi nance, on the other hand. In the circumstances of the global fi nancial crisis of 2008, the G-20 countries initiated an international reform of fi nancial regulation. According to G-20 decisions, international standardsetting organizations developed transnational regulatory regimes in the fi elds of banking, derivatives and bankruptcy resolution, and the states now implement these regimes in their jurisdictions. The so-called “soft law system”, which is not legally binding, allows the states to sustain national sovereignty in their fi nancial policy. The United States play a leading role in the international fi nancial reform, as well as in the shaping of the global fi nancial regulation system. The American regulators push for extraterritorial application of the US norms and take other unilateral actions on the international arena. The article also touches upon legitimacy problems of the emerging system of global fi nancial regulation. The most important constrains are the excessive infl uence of the fi nancial industry (“regulatory capture”), the weakness of civil society participation, and also the fact that for the rest of the world the American norms lack legitimacy, as they are adopted by regulators assigned by offi cials elected by population of a foreign territory.